PENERAPAN KOMUNIKASI TERAPEUTIK DALAM PENANGANAN PASIEN GANGGUAN JIWA DI RUMAH SAKIT JIWA PROVINSI BALI - TIRTAWATI, ANAK AGUNG RAI (Widya Accarya, 2017)
ABSTRACTÂ Â Â Â Â Â Â Â Â Â Â Â Â Â Â  Therapeutic communication is one way that can be used to help the healing process of the patient. This research was conducted to see the implementation of therapeutic communication in handling mental disorder patient according to Standard Operational Procedure (SOP) at Bali Provincial Mental Hospital 2017. The formulation of the problem is "How is the application of therapeutic communication in handling mental patients in Mental Hospital of Bali Province"Â Â Â Â Â Â Â Â Â Â The study is located in RSJ Bali Province which is a government hospital located in Bangli Regency. This research uses qualitative approach and object approach method using empirical approach. Selection of research subjects using purposive sampling which amounted to 13 nurses and methods of data collection using observation techniques, questionnaires, unstructured interviews and documentation. This study uses descriptive statistical analysis techniques used to examine the percentage of the percentage, which is then deepened with a qualitative study.Â Â Â Â Â Â Â Â Â Â The result of the research on the application of therapeutic communication in phase I (orientation phase) between the nurse and the mental disorder patient is 71% of the results in phase II (work phase) is 77%, then the result of research on the application of therapeutic communication in phase III (termination phase) is 67%. In addition to the above three phases, therapeutic attitudes of nurses and communication techniques are also investigated. The results of research on the application of therapeutic attitude of nurses in conducting therapeutic communication in mental disorder patients is 88% and nurse communication technique in applying therapeutic communication is 92%. In general, the results of research on the application of therapeutic communication in the treatment of ganggguan soul patients at RSM Jiwa Bali Province has been implemented optimallyÂ Keywords: Therapeutic Communication, Mental DisordersÂ ABSTRAKÂ Â Â Â Â Â Â Â Â  Â Komunikasi terapeutik merupakan salah satu cara yang dapat digunakan untuk membantu proses penyembuhan pasien. Penelitian ini dilakukan untuk melihat penerapan komunikasi terapeutik dalam menangani pasien gangguan jiwa sesuai Standar Operasional Prosedur (SOP) di Rumah Sakit Jiwa Provinsi Bali tahun 2017.Rumusan masalahnya adalah â?? Bagaimana penerapan komunikasi terapiutik dalam menangani pasien gangguan jiwa di Rumah sakit Jiwa Provinsi Bali â??Â Â Â Â Â Â Â Â Â  Penelitian berlokasi di RSJ Provinsi Bali yang merupakan rumah sakit pemerintah bertempat Â di Kabupaten Bangli. Penelitian ini menggunakan pendekatan kualitatif dan metode pendekatan objek menggunakan pendekatan empiris. Pemilihan subjek penelitian menggunakan purposive sampling yang berjumlah 13 perawat dan metode pengumpulan data menggunakan teknik observasi, kuesioner, wawancara tidak terstruktur dan dokumentasi. Penelitian ini menggunakan teknik analisis statistikÂ  deskriptif yang digunakan sebatas mengkaji besaran presentase, yang kemudian diperdalam dengan kajian secara kualitatif.Â Â Â Â Â Â Â Â Â  Hasil penelitian terhadap penerapan komunikasi terapeutik pada fase I (fase orientasi) antara perawat dengan pasien gangguan jiwa ialah sebesar 71% hasil pada fase II (fase kerja)Â  ialah sebesar 77%, kemudian hasil penelitian pada penerapan komunikasi terapeutik pada fase III (fase terminasi) ialah sebesar 67%. Selain ketiga fase di atas, sikap terapeutik perawat dan teknik komunikasi juga diteliti. Hasil penelitian terhadap penerapan sikap terapeutik perawat dalam melakukan komunikasi terapeutik pada pasien gangguan jiwa ialah sebesar 88% dan teknik komunikasi perawat dalam menerapkan komunikasi terapeutik ialah sebesar 92%. Secara umum hasil penelitian terhadap penerapan komunikasi terapeutik dalam penanganan pasien ganggguan jiwa di RSJ Jiwa Provinsi Bali penerapannya telah terlaksana secara optimalÂ Kata Kunci : Komunikasi Terapeutik, Gangguan Jiwa